An Study of the Competitiveness of the Spanish Ceramic Tile Industry. - Baldomero Segura-Garciadel Rio; Marna Del Val Segarra-Opa (European Regional Science Association (ERSA), 2006)
The main objective of the research project is to increase the competitiveness of the Spanish ceramic tile industry and, in this paper, we make a first approach to the state of the art in order to generate a theoretical model of study. This sector faces an increasing competition from other countries. Nowadays, the sector has access to a great deal of technological capacity and needs to diversify and differentiate its products. The precise objectives that we wish to pursue are the following: First, we intend to identify the resources and capacities of the different companys' behaviour and to evaluate the impact of industrial concentration, with the aim of developing a model that would allow us to propose new competitive strategies.
Keywords: 330